2009
DOI: 10.1007/bf03181877
|View full text |Cite
|
Sign up to set email alerts
|

Splash formation by a spherical body plunging into water

Abstract: Splashes caused by a spherical body plunging into water were investigated experimentally using a high speed CMOS camera. We categorized types of splash according to impact velocities of the sphere. Three types of splash were found: Type-I is a thin spire-type splash, Type-II is a mushroom-type splash with many droplets, and Type-III is a crown-type splash with many droplets. The reaction to the concave water surface attached to the sinking sphere is a cause of the Type-I splash. The film flow climbing up the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…In a previous work [4], we confirmed that contaminants common to tap water do not affect splash formation. To acquire sequential side-view images of splash formation, we used a high-speed CMOS camera (Vision Research Inc., Phantom v7.1) set at 4000 fps.…”
Section: Splash From Inanimate Objectssupporting
confidence: 83%
See 4 more Smart Citations
“…In a previous work [4], we confirmed that contaminants common to tap water do not affect splash formation. To acquire sequential side-view images of splash formation, we used a high-speed CMOS camera (Vision Research Inc., Phantom v7.1) set at 4000 fps.…”
Section: Splash From Inanimate Objectssupporting
confidence: 83%
“…The maximum film velocity for the hydrophilic object at V i = 3.1 m/s is more than twice that for s = 0 (i.e., acrylic object), which we attribute to the film separating from the surface of the object [4]. The film separates when the centrifugal force acting on the film becomes greater than the surface tension of the film [4] [15]. The film velocity increases with swelling, which indicates that hydrophilicity is related to splash formation.…”
Section: Effect Of Splash Formation With a Surface Conditionmentioning
confidence: 72%
See 3 more Smart Citations